CONVERGENCE OF NANO-, BIO-, INFO-, COGNITIVE TECHNOLOGIES AND E-CULTURE - Sergey I. Rodzin; Inna N. Titarenko (Открытое образование (Москва), 2016)
The article analyzes the convergence of nano-, bio-, info- and cognitive technologies. We highlight the close relationship of such notions as “e-culture”, “consciousness”, “artificial intelligence”. Artificial intelligence technology is the meta-NBIC-complex itself. Electronic infrastructure of intellectual activity - the essence of artificial intelligence and artificial intelligence technologies play a meta-level role of NBIC- technologies, being significant for e-culture. Development of science, technology, and education suggests that in the future perhaps a radical transformation in human beings is not only the material world, but also a subjective reality.